Nobiletin Attenuates Anesthesia/Surgery-Induced Neurocognitive Decline by Preserving the Expression of Clock Genes in Mice - Sun, Zhuonan; Yang, Ning; Jia, Xixi; Song, Yanan; Han, Dengyang; Wang, Xiaoxiao; Sun, Jie; Li, Zhengqian; Zuo, Zhiyi; Guo, Xiangyang (Frontiers in Neuroscience, 2022)
Postoperative cognitive dysfunction (POCD) is commonly observed during postoperative period and significantly affects the prognosis of patients. Neuroinflammation plays a vital role in the pathogenesis of POCD. Despite laboratory and clinical research over the past decades, practical pharmacological strategies for the treatment and prevention of POCD are not yet available currently. Nobiletin (NOB) is a natural polymethoxylated flavone. As an enhancer of the clock protein retinoic acid receptor-related orphan receptors (RORs), NOB has been shown to attenuate inflammation and improve cognitive decline. We speculate that NOB is a candidate for the treatment and prevention of POCD. In this study, we investigated whether and how NOB affected surgery-induced neuroinflammation and POCD in adult CD1 mice. NOB pretreatment suppressed exploratory laparotomy-induced systemic inflammation and neuroinflammation in a dose-dependent manner (< 50 mg/kg), and attenuated POCD. Moreover, NOB dose-dependently reversed the decrease of brain and muscle aryl hydrocarbon receptor nuclear translocator-like (ARNTL) protein 1 (Bmal1, also known as Arntl1) and Rorsexpression induced by exploratory laparotomy. The expression of Bmal was negatively correlated with tumor necrosis factor-TNF-. Our results suggest that NOB attenuated POCD, possibly via preserving the expression of Bmal and Rors,and inhibiting inflammation.